2012
DOI: 10.1084/jem.20110079
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factor 2 rapidly induces interleukin 33 to promote type 2 immunity during allergic asthma and hookworm infection

Abstract: The repair protein trefoil factor 2 promotes Th2 responses to helminth infection and allergens in part by inducing IL-33.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
182
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(189 citation statements)
references
References 82 publications
(141 reference statements)
5
182
1
1
Order By: Relevance
“…More recently, we and others have shown that IL-33 is also produced from myeloid lineage cells within hours of pathogen exposure (8,14), which is consistent with a hypothesis that IL-33 functions as an "alarmin" that instructs adaptive immune responses (12). Our demonstration that IL-33KO mice were highly susceptible to both primary and secondary N. brasiliensis infection is consistent with reciprocal experiments that demonstrated IL-33 administration promoted the rapid expulsion of the gastrointestinal helminth T. muris (16).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…More recently, we and others have shown that IL-33 is also produced from myeloid lineage cells within hours of pathogen exposure (8,14), which is consistent with a hypothesis that IL-33 functions as an "alarmin" that instructs adaptive immune responses (12). Our demonstration that IL-33KO mice were highly susceptible to both primary and secondary N. brasiliensis infection is consistent with reciprocal experiments that demonstrated IL-33 administration promoted the rapid expulsion of the gastrointestinal helminth T. muris (16).…”
Section: Discussionmentioning
confidence: 97%
“…At d 3 postinfection, IL-13-producing CD4 + T cells expand within the mediastinal lymph nodes (14), but this population does not accumulate within lung tissues until d 6 postinfection. IL-33 deficiency also significantly decreased both the percentage and number of lung IL-13 + CD4 + T cells during secondary immune responses, but IL-33 was not essential for expanding IL-4-producing CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, TFF2 has been shown to be essential in the regulation of IL-33 release at mucosal surfaces (18). Increased susceptibility to Yersinia enterocolitica was found in TFF2-knockout mice, which died following infection (19).…”
mentioning
confidence: 99%